2014
DOI: 10.1158/1940-6207.capr-14-0054
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Inhibits Endometrial Cancer Invasiveness by Inhibiting the TGFβ Pathway

Abstract: Increased expression of TGFb isoforms in human endometrial cancer correlates with decreased survival and poor prognosis. Progesterone has been shown to exert a chemoprotective effect against endometrial cancer, and previous animal models have suggested that these effects are accompanied by changes in TGFb. The goal of this study was to characterize the effect of progesterone on TGFb signaling pathway components and on TGFb-induced protumorigenic activities in endometrial cancer cell lines. Progesterone signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 48 publications
6
37
0
Order By: Relevance
“…Previously we have shown enhanced proliferation and invasive potential of endometrial cells in response to TGF-β1 [38]. Here we substantiated the direct interaction between Nestin and TGF-β in Nestin overexpressing cells by demonstrating a marked increase in Nestin expression which was associated with enhanced proliferation and invasive potential in response to TGF-β1 exposure.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previously we have shown enhanced proliferation and invasive potential of endometrial cells in response to TGF-β1 [38]. Here we substantiated the direct interaction between Nestin and TGF-β in Nestin overexpressing cells by demonstrating a marked increase in Nestin expression which was associated with enhanced proliferation and invasive potential in response to TGF-β1 exposure.…”
Section: Discussionsupporting
confidence: 85%
“…We and others have previously shown that TGF-β signaling pathway is activated in endometrial cancer cells [22, 23, 38]. Our findings suggest that elevated levels of Nestin in endometrial cancer cells can stimulate cell proliferation and invasion by stimulating TGF-β signaling pathway.…”
Section: Discussionsupporting
confidence: 66%
“…We previously reported that progesterone-mediated upregulation of vitamin D receptor (VDR) levels increases calcitriol-induced growth inhibition in endometrial cancer cells [9, 10]. Here, we expand upon our previous work by examining the effects of calcitriol and progesterone, both alone and in combination, on CYP24A1.…”
Section: Introductionmentioning
confidence: 84%
“…Combining a low dose of progesterone with a low dose of calcitriol, a vitamin D metabolite, might be more effective for treating endometrial cancer than higher doses of either agent alone. In vitro and in vivo studies from our laboratory and others have shown that progesterone and other chemopreventive agents enhance the antitumor effects of calcitriol [710]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, progesterone was shown to inhibit basal and TGFB1 induced cancer cell viability and invasion, which was accompanied by increased E-cadherin and decreased vimentin expression (Bokhari et al 2014). Chaudhry et al (2014) observed that TGFB upregulates the expression of prostate apoptosis response-4, a tumor suppressor protein, with simultaneous induction of EMT in endometrial and cervical cancer cells.…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%